Faktor-Faktor Yang Mempengaruhi Keputusan Mahasiswa Menggunakan Financial Technologi OVO (Studi Kasus Pada Mahasiswa Manajemen Bisnis Syariah Fakultas Agama Islam UMSU Semester VIII T.A 2021/2022) - Shafira, Dwi Laila; Amsari, Syahrul (Universitas Labuhanbatu, 2022)
Users of OVO financial technology have not been evenly distributed, including among students of Islamic Business Management Faculty of Islamic Religion Semester VIII T.A 2021/2022, Then there is a lack of understanding of students in using OVO financial technology and students feel there is no need when using OVO financial technology so that this study aims to determine the factors anything that can influence student decisions in using OVO financial technology. In this study, the researcher uses quantitative research which will find knowledge that uses data in the form of numbers as a way of finding information about what they want to know. A quantitative approach was chosen to explain the effect of student interest in using OVO financial technology. The results of this study explain that workload, compensation, commitment have a positive and significant effect simultaneously (simultaneously) on the decisions of Sharia Business Management Students, Faculty of Islamic Religion, UMSU semester VIII using financial technology OVO. This can be seen from the multiple linear regression analysis through the F test which is positive with an Fcount value of 228.638 with a Ftable value of 3.18 with a significant level of 0.000. Confidence, lifestyle and promotion factors simultaneously have a positive and significant effect on the decisions of Islamic Business Management Students Faculty of Islamic Religion UMSU semester VIII uses financial technology OVO. The most dominant variable influencing the decision of Islamic Business Management Students, Faculty of Islamic Religion, UMSU semester VIII to use OVO financial technology is lifestyle factors.